Budget impact of prophylactic treatment of rVIII-SingleChain in moderate and severe hemophilia A in Italy. (31st December 2023) - Di Brino, Eugenio; Yan, Songkai; Tomic, Radovan; Panebianco, Marco; Dlotko, Ewa; Stern, Lee; Basile, Michele; Rumi, Filippo; Cicchetti, Americo; Marino, Renato
Abstract: Introduction: rVIII-SingleChain, a recombinant factor VIII (rFVIII), has demonstrated safety and efficacy in patients with hemophilia A in clinical trials and real-world evidence. This analysis aimed to estimate the potential budget impact of increasing the usage of rVIII-SingleChain for the prophylactic treatment of hemophilia A over 3 years in Italy. Methods: Patients with moderate and severe hemophilia A receiving prophylaxis were included in the analysis. Epidemiological data were obtained from published literature. Mean product consumption and mean annual bleeding rate for rVIII-SingleChain, rFVIIIFc, octocog alfa and BAY 81-8973 were based on pooled real-world data from Italy, Germany and US. A budget impact model has been developed in order to compare two scenarios: a base-case scenario where current rVIII-SingleChain shares are kept constant over 3 years and an alternative scenario where rVIII-SingleChain shares increase by taking from other rFVIII products. Analysis 1 was based on the current Italian list prices and Analysis 2 considered current regional acquisition prices for both scenarios. Results: Annually, adult patients treated with rVIII-SingleChain prophylaxis are expected to consume 324, 589 units per patient, resulting in annual costs of €240, 196 per patient. In Analysis 1, comparing the base case (constant market share of 9% rVIII-SingleChain over time) with the alternative scenario (higher rVIII-SingleChain market share and increasing from 15% in the first year to 25% in the third year), the total expenditure for prophylaxis using rFVIII products is expected to decrease by €1.4 million in Year 1, by €3.1 million in Year 2 and by €5.4 million in Year 3. In Analysis 2 based on regional prices, the results remained consistent. Discussion/Conclusion: This analysis suggests that increasing utilization of rVIII-SingleChain in hemophilia A patients may lead to cost savings as a result of reduced consumption with uncompromised efficacy in bleed protection. PLAIN LANGUAGE SUMMARY: Why was the study done? Hemophilia A is a rare inherited bleeding disorder. People with severe hemophilia are more likely to bleed compared to people without hemophilia and bleeds can occur spontaneously or in response to trauma. Patients are treated with medication to reduce the chance of bleeding. However, the cost of treating patients with hemophilia can be high and place demands on the healthcare system. What did we do and find? This study looked at the cost of treating people with hemophilia in Italy and used a type of economic analysis (called budget impact modelling) to estimate the effect of increasing the use of a particular medication (rVIII-SingleChain), compared to other medications that are available. Different variations of the model were tested to compare a range of scenarios. The results of this analysis suggested that increasing the use of rVIII-SingleChain may lead to cost-savings for the Italian healthcare system, compared to using the other currently available treatments. This analysis suggests that the use of rVIII-SingleChain enables people with hemophilia A to remain protected from bleeds, whilst using less product compared to other available medications. What is the influence of this study on the wider field? This type of analysis can be useful to healthcare systems, to guide the decision-making process regarding which medications to use or when making decisions related to healthcare policy.